Pseudo-continuous arterial spin labeling MRI study of patients with obsessive–compulsive disorder. (30th September 2020) - Ota, Miho; Kanie, Ayako; Kobayashi, Yuki; Nakajima, Aiichiro; Sato, Noriko; Horikoshi, Masaru
Highlights: OCD patients showed the rCBF changes in cortico-striato-thalamo-cortical pathway. OCD patients decrease the gray matter volume in the hippocampus. Anterior cingulate cortex volume were correlated with the Y-BOCS score. Abstract: Arterial spin labeling (ASL) magnetic resonance imaging is a novel technique that can measure regional cerebral blood flow (rCBF). Here we used pseudo-continuous ASL (pCASL) to examine the structural and functional imaging data in patients with obsessive-compulsive disorder (OCD). We estimated the gray matter volume imaging and pCASL imaging data by means of a voxel-by-voxel statistical analysis. We evaluated the differences of rCBF and gray matter volume between the OCD patients and healthy subjects. We detected a significant rCBF reduction in OCD patients in the right posterior cingulate extending to the lingual gyrus, thalamus, and hippocampus, and a significant increase in the left temporal gyrus and left frontal white matter region, compared with healthy subjects. We also observed a significant reduction in gray matter volume of OCD patients in the right hippocampus. We also estimated the correlation between the clinical severity of OCD and the rCBF and gray matter volumes, and found significant negative correlations between the severity of illness and the regional gray matter volume in the bilateral anterior cingulate corti. Our study demonstrated significant changes of rCBF in the cortico-striato-thalamo-cortical pathway around the hippocampus in OCD patients. These findings may help to elucidate the pathogenesis of OCD.